2013 IEEE International Conference on Industrial Engineering and Engineering Management 2013
DOI: 10.1109/ieem.2013.6962498
|View full text |Cite
|
Sign up to set email alerts
|

Configuration of high performance apartment buildings renovation: A constraint based approach

Abstract: This paper looks at the possibility of configuring high performance renovation of apartment buildings by the use of a constraint satisfaction problem (CSP). A new thermal envelope wraps the whole building and allows it to achieve a really low energy performance of 25 kWh/m²/year. This new thermal envelope is composed of rectangular panels, always comprising insulation and cladding, and sometimes including, in addition, doors, windows or solar modules. The panels can be fixed directly onto the walls or onto a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Therefore, ETO product configuration cannot be supported by a PCS in line with previous ATO/MTO hypotheses and definitions. In the literature, many studies have been reported in the field of ATO/MTO product generic modeling, see [4], [8], [6] or [9]. However, much fewer concern ETO products, see [7], [10].…”
Section: Towards a Metric Between Engineering To Order And Assemble/mmentioning
confidence: 99%
“…Therefore, ETO product configuration cannot be supported by a PCS in line with previous ATO/MTO hypotheses and definitions. In the literature, many studies have been reported in the field of ATO/MTO product generic modeling, see [4], [8], [6] or [9]. However, much fewer concern ETO products, see [7], [10].…”
Section: Towards a Metric Between Engineering To Order And Assemble/mmentioning
confidence: 99%
“…One strategy for reducing such energy consumption lies on buildings thermal retrofit achieved either by an internal or an external insulation [9]. Among several options [9], an external insulation may be based on covering the entire building with an envelope made out of rectangular wood-made panels [7,23]. However, some difficulties are present when targeting such renovation in industrial proportions, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the problem lies on the configuration of rectangular parameterizable panels, and their attaching devices called fasteners, that must be allocated over the facade surface in order to provide an insulation envelope [2]. A configuration solution is a plan which satisfies optimization criteria and a set of constraints (such as geometrical, weight or resources constraints) provided by users and the facade itself.…”
Section: Introductionmentioning
confidence: 99%